Ambidexterity and Knowledge Strategy in Major Projects: A Framework and Illustrative Case Study. Issue 5 (October 2014) - Turner, Neil; Maylor, Harvey; Lee-Kelley, Liz; Brady, Tim; Kutsch, Elmar; Carver, Stephen
We develop a framework to analyze the multilevel knowledge requirements of complex, major projects in terms of ambidexterity –-the ability to exploit (refine existing knowledge) and explore (develop new knowledge). This is an important theme within the wider literature, yet practical operationalization methods for managers and researchers are not evident. We demonstrate the ambidexterity view through an illustrative case study of telecommunications delivery for the London 2012 Olympic Games and show how these concepts can be used to create an effective knowledge strategy. We offer a structure for the analysis of knowledge utilization in projects.